A discourse analysis of six stories based on the thematic progression factor: Halliday and Matthiessen's functional grammar approach (2014) - seyed abbas navabi sohi; ferdous aghagolzade; ahmad mohseni (زبان پژوهی, 2025)
1. Introduction Achieving successful communication in language involves the writer's organization of meaning as messages in clauses and texts, and the reader's identification of them to interpret the messages of the texts appropriately. Therefore, one of the concerns of readers has always been how to uncover the textual and discoursal meanings of texts, especially literary texts. Fortunately, since the 1970s, functionalism has had a significant influence on analyzing literary texts, and since 1994, it has been used as an approach to analyzing texts. Based on the textual metafunction in functional grammar, thematic systems organize meanings in clauses and texts. Thematic structures are responsible for organizing meanings in clauses, and thematic patterns are responsible for organizing meanings in texts so that they not only create cohesion and coherence but also convey the intended messages.  Accordingly, this study aims to analyze the texts of short stories based on the thematic progression factor in textual metafunction to identify the progression patterns and the discoursal factors that influence them. To do this, the present paper relies on Halliday and Matthiessen's functional grammar (2014), Shieh and Lin’s seven thematic progression patterns (2011), and a descriptive-analytic method. Correspondingly, the research question of this study is how thematic systems contribute to coherence and the conveyance of messages in six Persian short stories. Based on this question, the related research hypothesis is that thematic systems, by using thematic patterns in the story texts, achieve coherence and facilitate the conveyance of messages, thereby representing textual and discoursal meanings. There is some literature on progression patterns and a significant body of research on theme analysis. For example, Marfuaty and Wahyudi (2015), in their investigation of thematic progression patterns in the opinion section of the Jakarta Post, concluded that the most frequent pattern and theme were linear pattern and topical theme. Rahnemoon et al. (2019) investigated the themes of 643 clauses of English news texts and their Persian translation, finding that there were no significant differences between the progression patterns in English and Persian, except for the simple linear pattern. Larasati et al. (2022) used thematic structure and progression patterns to investigate Boris Johnson's speech and showed that the most dominant topical theme and pattern were circumstantial adjuncts and the constant pattern, respectively. These studies demonstrate the presence of different kinds of themes in clauses and thematic patterns in texts. However, the above studies are mostly structure-based rather than discourse-based. Nevertheless, the present study offers several advantages compared to previous research. In addition to using seven thematic patterns instead of two, three, or four, this research is discourse-based and investigates the discourse factors influencing the use of these patterns in the six short story texts.